Eco-Warning in the Legend of Lake Tondano: An Ecocritical Study of Tourism Literature - Sabrina Wardatul Jannah Husain; Muhammad Ilham Ali; Herminus Efrando Pabur; Ceisy Nita Wuntu (LITERA KULTURA : Journal of Literary and Cultural Studies, 2025)
This study examines the Legend of Lake Tondano as an instrument of ecological literacy in the context of sustainable tourism through Greg Garrard's ecocritical approach, specifically the concept of eco-warning. The modern tourism industry often exploits local narratives for commercial purposes without considering the substantive environmental messages they convey. This phenomenon creates a gap between the idealistic narrative promoted to tourists and the reality of ecological degradation experienced by Lake Tondano, including silt deposition, water hyacinth growth, and declining water quality. This study aims to analyze the dimensions of ecological warning in the legend and explore its potential as a medium for critical reflection on environmental conditions. Using descriptive qualitative methods with close reading techniques, this study identifies narrative units containing representations of ecological warning based on Garrard's theoretical framework. The analysis focuses on three main aspects: apocalyptic rhetoric, the concept of wilderness, and representations of human-nature relationships. This study proposes a reinterpretation of the legend as an instrument of ecological literacy that emphasizes ecologically conscious tourism, the development of thematic tourism routes that connect past apocalyptic events with present-day ecological challenges, and infrastructure policies that respect the active role of nature.